Towards Conservation of Medicinal Plant Lore of Indian Arid Zone - Mertia, R. S.; Nagarajan, M. (Indian Forester, 2003)
The Indian desert flora has an important place in the field of desert floristics , as it support western as well as eastern elements along with higher percentage of endemic plants. There are numerous plant species which are confined to western bulge of our country and are less known at this point of time in other areas. However species viz; Commiphora wightii (Gugal) and Tephrosia falciformis (Rati Biyani) are now under application in the field of medicine. Besides mitigating the ethno-medicinal needs of the desert peasantry , these species offer potential for conservation and optimum use in the field of medicines. The results of the present study clearly infer the possibilities of conservation of the some of the species investigated. However , detailed study on their physio-chemical composition would provide more information on the economic values of individual plant species. Efforts are continuing on investigation of many more species , which would provide valuable information on different aspects of conservation , and propagation of endemic species for better eco-environment in the extreme arid regions along with their medicinal value.